Weeds Interference in Pequi Plants - MARTINS,D.A. (2018)
ABSTRACT: Pequi plants are native fruit species of the Cerrado and is at risk of extinction due to the destruction of native vegetation and the extraction of their fruits. Because this species has a long juvenile period, it becomes susceptible to the interference of weeds, mainly forage grass. This research aimed to evaluate the effects of forage grass species coexisting with small seedlings. The treatments, arranged in a factorial scheme, consisted of three weed species(Melinis minutiflora, Paspalum notatumandUrochloa decumbens)coexisting in four densities (1, 2, 3, and 4 plants per pot) with pequi plants. As an additional treatment a pequi plant was cultivated free of coexistence. The physiological variables photosynthetic rate (A), stomatal conductance (gs), transpiration rate (E) Ci/Ca relation, the effective quantum yield of PS II, transport rate of electrons and non-photochemical quenching, and growth variables: height (PH), Leaf area (LA) and dry matter (DM) were affected by weed coexistence.U. decumbenspromoted greater intensity interference with pequi plants. The degree of interference was greater with increasing density of weeds, with linear decreasing behavior for the variables A, gs, E, PH, LA, MD, stem diameter and number of leaves of pequi plants.